PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA PEGAWAI - Rosdiana H, Putri Vera; Mastuti, Dian Nur (STIE AUB Surakarta)
This study aims to test and analyze influence the use of information systems accounting, quality of information systems accounting security system accounting information and supporting facilities information systems accounting on performance employees of PT.KMA Solo. Analysis of the data used was classic test the assumption consisting of normality test, multikolinearitas test, as well as test heteroskedastisitas autokorelasi. An analysis of the data used was classic test the assumption consisting of normality test, multikolinearitas test, as well as test heteroskedastisitas autokorelasi.uji test a hypothesis that is used is linear regression analysis worship of idols, partial test (t) test, as well as a test of the coefficients determinan (R2). Based on the results of data analysis prove that; the utilization of accounting information system have positive and significant of the performance of employees of PT .KMA Solo; the quality of information system accounting have positive and significant of the performance of employees of PT .KMA Solo; security accounting information system influential positive and significant on performance employees of PT.KMA Solo; means of support information systems accounting influential positive and significant on performance employees of PT.KMA Solo.Test R2 shows that variable the use of accounting information system, the quality of information systems accounting, the security system information accounting and means of support information system can explain on variables the employee performance the remaining influenced by other variables that are not using in the study.Keyword : Use Of Accounting Information System, Quality Of Information Systems Accounting, Security Accounting Information System, Supporting Facilities Accounting Information System, Job Performance